2009
DOI: 10.1242/jcs.041665
|View full text |Cite
|
Sign up to set email alerts
|

Necdin is expressed in cachectic skeletal muscle to protect fibers from tumor-induced wasting

Abstract: Skeletal muscles of subjects with advanced cancer undergo progressive wasting, referred to as cachexia. Cachexia is an important area for medical research because strategies proposed until now have yielded little benefit. We have recently identified necdin as a key player in fetal and postnatal physiological myogenesis and in muscle regeneration. Here we show that necdin is selectively expressed in muscles of cachetic mice and prove that its expression is causally linked to a protective response of the tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…They differentiate into myotubes under low serum conditions; treatment with TGF-b commits them to differentiate into smooth muscle; treatment with BMP2 commits them to differentiate into osteocytes, as expected (49). Satellite cells were isolated as described (50). Polarized macrophages were propagated as described (51).…”
Section: Cell Culture and Mediamentioning
confidence: 97%
“…They differentiate into myotubes under low serum conditions; treatment with TGF-b commits them to differentiate into smooth muscle; treatment with BMP2 commits them to differentiate into osteocytes, as expected (49). Satellite cells were isolated as described (50). Polarized macrophages were propagated as described (51).…”
Section: Cell Culture and Mediamentioning
confidence: 97%
“…Subsequently, the expression of myogenin and MRF4 (MRF members) is up-regulated in the cells beginning their terminal differentiation program, followed by a permanent exit from the cell cycle, the activation of muscle specific proteins, such as sarcomeric myosin, Defective skeletal muscle regeneration secondary to the potent inhibiting action of TNF-· has been shown to contribute to muscle wasting in a mouse model of cachexia (7,8). Indeed, we have demonstrated that necdin, a member of the MAGE family, plays an important role in skeletal muscle growth and repair in vivo, and is selectively expressed in the muscles of cachetic mice and that its expression is causally linked to a protective response of the tissue against tumor-induced wasting, the inhibition of myogenic differentiation and fiber regeneration (9). Despite such experimental evidence, studies on the role of muscle regeneration or defective regeneration in humans with cancer are still lacking.…”
Section: Introductionmentioning
confidence: 85%
“…This process is mainly linked to the activation of both IKKß/NF-κB-dependent and -independent pathways triggered by the increased signaling of TNF-· (13). TNF-· has been also shown to inhibit in vitro and in vivo myogenesis (7,9) as well as muscle regeneration by inhibiting cell fusion and by up-regulating caspase activity in myogenic stem cells (8). We have previously shown that the MAGE protein necdin is selectively expressed in the muscles of cachectic mice and have proven that its expression is causally linked to a protective response of the tissue against the tumor-induced wasting of myogenic differentiation and the inhibition of fiber regeneration (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Furthermore, we recently showed, in a mouse model and in human patients, that necdin counteracts muscle wasting specifically induced by cachexia, a pathology in which atrophy is associated with tumor load. 12,13 In this context, necdin exerts its protecting effect by interfering with tumor necrosis factor alpha (TNFa)-activated signaling at various levels and it is associated with a regenerative response of the muscle to wasting.…”
mentioning
confidence: 99%